2014
DOI: 10.1002/2013ja018708
|View full text |Cite
|
Sign up to set email alerts
|

How does solar eclipse influence the complex behavior of midlatitude ionosphere? Two case studies

Abstract: This paper investigates the influence of two solar eclipses on the ionosphere complexity measures: Tsallis entropy, Rényi entropy, Hurst exponent, beta exponent, and fractal dimension. The study used GPS TEC measured at three locations in Japan during the solar eclipses of 22 July 2009 and 21 May 2012. This is the first effort to compare the complexity measures by comparing TEC time series of the eclipse day with those from the day before and the day after the eclipse. It was found from analysis of the TEC obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…When the chromosphere irradiance was assumed to be zero at totality, it was found that 30% coronal emission remaining at totality gave the best fit to the electron density variation at 150 km and C = 0.3 was used for all the calculations in this article. Some previous eclipse calculations have used the same obscuration factor for all EUV wavelengths (e.g., Unnikrishnan & Richards, ). This assumption does not lead to serious error for partial eclipses where there is substantial emission from the solar disk, but the effect is significant when there is near total obscuration of the disk.…”
Section: Resultsmentioning
confidence: 99%
“…When the chromosphere irradiance was assumed to be zero at totality, it was found that 30% coronal emission remaining at totality gave the best fit to the electron density variation at 150 km and C = 0.3 was used for all the calculations in this article. Some previous eclipse calculations have used the same obscuration factor for all EUV wavelengths (e.g., Unnikrishnan & Richards, ). This assumption does not lead to serious error for partial eclipses where there is substantial emission from the solar disk, but the effect is significant when there is near total obscuration of the disk.…”
Section: Resultsmentioning
confidence: 99%
“…Many different ionospheric models have been used to determine the effects of eclipses, such as the NCAR model (Roble et al, 1986; Salah et al, 1986), CTIP (Müller‐Wodarg et al, 1998), SUPIM (Bravo et al, 2020; MacPherson et al, 2000), TIME‐IGGCAS (Le et al, 2008a, 2008b; Le, Liu, Yue, & Wan, 2009; Le, Liu, Yue, Wan, & Ning, 2009; Le et al, 2010), SAMI3 (Huba & Drob, 2017), FLIP (Reinisch et al, 2018; Unnikrishnan & Richards, 2014), GITM (Cnossen et al, 2019; Wu et al, 2018), TIEGCM (Chen et al, 2019; Dang et al, 2018, 2020; Lei et al, 2018; Wang et al, 2019), WACCM‐X (McInerney et al, 2018), and an empirical ionospheric model based on measurements of the Millstone Hill incoherent scatter radar (ISR; Goncharenko et al, 2018). However, few studies estimate the ionospheric impacts prior to eclipses occurrence (Dang et al, 2020; Huba & Drob, 2017; Müller‐Wodarg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%